Memory of the Present: Empathy and Identity in Young Adult Fiction - Nikolajeva, Maria (Narrative Works, 2014)
Recent studies in cognitive literary criticism have provided scholars of literature with new, stimulating approaches to literary texts and neuroscientists with new insights about human emotions, empathy, and memory through evidence from fiction. What have so far been largely neglected are the implications of cognitive criticism for the study of literature targeting a young audience, whose theory of mind and empathic skills are not yet fully developed. A cognitive approach to children's and young adult literature has to meet several challenges less relevant in general fiction. Firstly, how is a young fictional character's consciousness represented by an author whose cognitive and affective skills are ostensibly superior? Secondly, how do texts instruct their young readers to employ theory of mind in order to assess both the young protagonist's emotions and their understanding of other characters' emotions (higher-order mind-reading)? Thirdly, how can fiction support young people's development of their theory of mind? The paper will discuss these issues with a particular focus on memory and identity, expressed textually through tense and narrative perspective. Drawing on work by Lisa Zunshine (2006) and Blackey Vermeule (2010), the predominantly theoretical argument will be illustrated by a contemporary young adult novel, Slated (2012), by Teri Terry.